Long Road to Baghdad a History of U.S. Foreign Policy from the 1970s to the Present. - Gardner, Lloyd C. (New York : New Press, 2010)
A sweeping and authoritative narrative, The Long Road to Baghdad places the Iraq War in the context of U.S. foreign policy since Vietnam, casting the conflict as a chapter in a much broader story of American diplomatic and military moves in the region. With'a keen grasp of sprawling subject matter' (Kirkus), Lloyd Gardner, one of the nation's premier diplomatic historians, illuminates a vital historical thread connecting Walt Whitman Rostow's defense of U.S. intervention in Southeast Asia, Zbigniew Brzezinski's renewed attempts to project American power into the'arc of crisis' (with Iran at i.
Print version record.
Keywords: Iraq War, 2003-2011 -- Causes; United States -- Politics and government -- 2001-2009.